Design Of A Main Substation Grounding System Based On Variations In Area and Number Of Electrodes - Panjaitan, Joel; Fitriani, Ayu; Hidayat, Jhoni; Pakpahan, Arnold; Muchlisin, Muhammad; Sirait, Regina (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
The function of the grounding system is to limit the voltage between equipment and the ground and neutralize the voltage that arises at the ground surface due to fault currents flowing in the ground. An unsafe grounding system can disrupt system reliability and human safety in the substation area. This research aims to simulate the design of a substation grounding system with the influence of variations in location and number of electrodes installed in grids and rods in swampy soil conditions with different soil resistivity values. The impact of these parameters is on the resistance value, touch voltage, and step voltage at a weight of 70 kg by using the CYMGRD application as a medium to see the effectiveness and optimization of whether the substation grounding system with variations in the outside area and variations in the number of electrode rods meets the requirements without exceeding safe limits on systems or humans. This grounding system design is designed for two cases, namely case 1: the maximum touch voltage and maximum step voltage values exceed the permitted touch voltage and maximum step voltage, so conditions like this are included in the criteria for being unsafe and can endanger personnel in the field. Case 2: the touch voltage and step voltage values are smaller than the permitted touch voltage and step voltage values, so this design is included in safe conditions and meets the criteria for a good and safe grounding system.